1989
DOI: 10.1016/0300-9629(89)90375-7
|View full text |Cite
|
Sign up to set email alerts
|

Hibernation in a monotreme, the echidna (Tachyglossus aculeatus)

Abstract: Abstract-1. The body temperatures of five echidnas in Australia's Southern Alps were monitored by radio telemetry from February to December 1987.2. All five hibernated throughout the winter, showing very low body temperatures (4-9°C, close to ambient) when torpid, compared with 28-33°C in a typical day during the active season.3. Spontaneous arousals from hibernation occurred every 2-3 weeks, during which body temperatures rose rapidly to over 30°C for several hours before dropping to be close to ambient again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 7 publications
3
45
0
Order By: Relevance
“…2 shows 4 consecutive years from one female. The data logger recordings confirm previous observations that echidnas are 'classical' hibernators (Grigg et al, 1989Grigg and Beard, 2000;Andersen, 1996, 2000), with bouts of deep torpor broken by periodic arousals to euthermia. Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…2 shows 4 consecutive years from one female. The data logger recordings confirm previous observations that echidnas are 'classical' hibernators (Grigg et al, 1989Grigg and Beard, 2000;Andersen, 1996, 2000), with bouts of deep torpor broken by periodic arousals to euthermia. Fig.…”
Section: Resultssupporting
confidence: 86%
“…When T values have been recorded in areas where b mean minimum temperatures in winter fall to 5 8C or lower (Australian Alps, Grigg et al, 1992Grigg et al, , 1989Tasmania, Nicol and Andersen, 1996;New England Tablelands, Falkenstein et al, 1999;south-east Queensland, Beard and Grigg, 2000) echidnas demonstrate a pattern of hibernation which closely resembles deep hibernation in other mammals: periods of deep torpor in which body temperatures fall to approximately 0.5 8C above ground temperature are broken by periodic arousals to normothermia. On Kangaroo Island, which is the mildest climatic area from which echidna T b data are available, (average minimum air temperatures in winter are 9 8C), Rismiller and McKelvey (1996) found minimum T values of approximately b 11 8C, and, compared to other areas, a later and much reduced hibernation period, with a small number of torpor bouts.…”
Section: Introductionmentioning
confidence: 99%
“…Calibrated temperature sensitive radio-transmitters (Sirtrack) coated with a smooth layer of inert wax were inserted into the abdominal cavities of these echidnas (two males and six females between 2.60 and 3.97 kg) via a midline laparotomy as described by Grigg et al (1989). The echidnas were marked with colour plastic tubing as described by Brattstrom (1973) and returned to their respective capture sites.…”
Section: Methodsmentioning
confidence: 99%
“…Field studies on the short-beaked echidna (Tachyglossus aculeatus) have shown lower and more variable body temperatures (T b ) than those usually associated with mammals ( [Augee et al, 1970, Grant, 1983, Grigg et al, 1989and Grigg et al, 1992a). T b in the short-beaked echidna characteristically cycles through 4-6 °C on a daily basis with a modal temperature of 30-32 °C ( [Grigg et al, 1992a]) and a skew in the distribution of T b towards the lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…T b cycles are usually correlated with activity, an increase in T b being associated with the onset of activity. In addition, the shortbeaked echidna has been shown to exhibit an array of body temperature patterns consistent with both short-and long-term torpor (also described as hibernation) ( [Grigg et al, 1989, Grigg et al, 1992a, Nicol and Andersen, 1996). The mostly aquatic platypus, Ornithorhyncus anatinus, also displays a daily cycle in T b , but smaller than in the short-beak (usually <2 °C) with a mode of 32 °C ( [Grigg et al, 1992b]).…”
Section: Introductionmentioning
confidence: 99%